2016
DOI: 10.1093/nar/gkw966
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of chromatin state and architecture byHOTAIRM1contributes to temporal collinearHOXAgene activation

Abstract: Thousands of long non-coding RNAs (lncRNAs) have been identified in mammals, many of which represent important regulators of gene expression. However, the mechanisms used by lncRNAs to control transcription remain largely uncharacterized. Here, we report on HOTAIRM1, a promising lncRNA biomarker in leukemia and solid tumors. We find that HOTAIRM1 contributes to three-dimensional chromatin organization changes required for the temporal collinear activation of HOXA genes. We show that distinct HOTAIRM1 variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 52 publications
11
68
1
Order By: Relevance
“…HOTAIRM1 has 2 transcript variants with 2 or 3 exons, with the first and last exons being shared. This lncRNA seems to undergo alternative splicing, and a previous study reporting on the role of HOTAIRM1 in the regulation of temporal collinear activation of HOXA genes in embryonic stem cells showed the major isoform to be the spliced form with all 3 exons [34]. On the contrary, in our breast cancer model system, we found that the spliced form with exons 1 and 3 was the predominant form.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…HOTAIRM1 has 2 transcript variants with 2 or 3 exons, with the first and last exons being shared. This lncRNA seems to undergo alternative splicing, and a previous study reporting on the role of HOTAIRM1 in the regulation of temporal collinear activation of HOXA genes in embryonic stem cells showed the major isoform to be the spliced form with all 3 exons [34]. On the contrary, in our breast cancer model system, we found that the spliced form with exons 1 and 3 was the predominant form.…”
Section: Discussioncontrasting
confidence: 52%
“…On the contrary, in our breast cancer model system, we found that the spliced form with exons 1 and 3 was the predominant form. Similarly, in acute myeloid leukemia (AML), the spliced form containing exons 1 and 3 was shown to be more prominent [34,35]. In both our system and the AML model, the spliced form containing exon 2 could not be detected.…”
Section: Discussionmentioning
confidence: 57%
“…HOTAIRM1 expression is activated by all-trans retinoic acid, which induces the differentiation of myeloid progenitor cells to granulocytes and mature myeloid cells [53]. HOTAIRM1 transcript also interacts and form complexes with transcripts of other key chromatin structure modulating proteins such as CBX1, PRC1 and PRC2 [242]. HOTAIRM1 was overexpressed in NPM1mutated AML.…”
Section: Clinical Significance Of Ncrnas In Leukemiamentioning
confidence: 99%
“…HOTAIRM1 lncRNA has been reported to participate in the regulation of multiple biological processes. [ 70,71 ] In myeloid cells, HOTAIRM1 was shown to induce the degradation of promyelocytic‐retinoic acid receptor alpha oncoprotein by promoting the formation of autophagosomes, resulting in the suppression of myeloid cell differentiation in acute promyelocytic leukemia cells. [ 72 ]…”
Section: Reagents Involved In Selective Protein Degradationmentioning
confidence: 99%